Bibliometric analysis of publications of research institutes SB RAS employees in the field of nanotechnologies during 2000–2010 based on the database Scopus - T. V. Busygina (Библиосфера, 2012)
On the basis of the database Scopus bibliometric research of documentary-information flow on nanotechnology in SB RAS is carried out. The author has structured types and kinds of publications, their dynamics during 2000–2010, and the list of the authors with the largest number of publications. The circle of journals with the largest number of documents on subjects considered is submitted, as well as the leading collaborating organizations and countries.